Analysis of the Multiplier Effect of the Golomori Sunset Run Event on the Local Economy - I Nengah Dasi Astawa; Reynaldo Angga Siagian; Roseven Rudiyanto; Ni Wayan Noviana Safitri; Made Satria Pramanda Putra (Pusat Penelitian dan Pengabdian Politeknik eLBajo Commodus, 2025)
The Golo Mori Sunset Run was evaluated for its economic, socio-cultural, and environmental impacts. The event generated a strong economic multiplier effect, with each unit of investment producing more than twice the level of local economic activity, primarily driven by participant spending, local MSME engagement, and volunteer compensation, while indirect and induced effects further circulated benefits within the community. Socio-culturally, the event promoted healthy lifestyles, strengthened social interactions, and highlighted local culture through participation by sports communities and Manggarai cultural performances, although volunteer gender distribution revealed both traditional role segmentation and areas of inclusivity. Environmentally, initiatives such as a ban on single-use plastics and the provision of refill stations were positively received, yet gaps in waste management, including limited trash bins and reliance on internal cleaning teams, were noted. Overall, the Golo Mori Sunset Run demonstrates how a sports event can simultaneously stimulate local economic growth, foster socio-cultural engagement, and encourage environmentally responsible practices, contributing to sustainable community development.